Thermal Performances of UHMWPE/BN Composites Obtained from Different Blending Methods - Yiyou Guo; Changlin Cao; Huibin Cheng; Qinghua Chen; Baoquan Huang; Fubin Luo; Qingrong Qian (Advances in Polymer Technology)
UHMWPE/BN composites were prepared by solvent mixing (SM) in this work, then were characterized by scanning electron microscope (SEM), Raman mapping, differential scanning calorimeter (DSC), thermogravimetric analysis (TG), and thermal conductivity meter to study the morphology, filler distribution, segregated structure, and thermal stability as well as thermal conductivity. Compared to the traditional melt mixing (MM), SM followed by molding contributes to the construction of segregated structures in UHMWPE composite. This segregated structure can greatly improve the thermal conductivity of the composites. The segregated structure of composites prepared by MM is destroyed by shearing. Moreover, the thermal stability of composites by SM is improved with the increment of BN content, which is better than that of samples by MM, probably resulting from the barrier function of the segregated structure.